In/zeolites prepared by oxidative solid state ion exchange (OSSIE): Surface species and structural characterization - Zamaro, Juan Manuel (2010)
The characteristics of surface indium species and the transformations suffered by In/zeolite catalysts during the indium incorporation process by oxidative solid state ion exchange (OSSIE) are studied. This method causes a progressive dealumination of mordenite during the exchange process evidenced by 29Si MAS NMR and 27Al MAS NMR, producing a high proportion of octahedral aluminum that is further distorted at higher temperatures. However, ZSM5 is a much more stable framework for this exchange process. Exchanged indium (InO)+ and highly-dispersed indium oxide species (InxOy) have the ability of adsorbing NO and further oxidizing it towards NO2. Together with these dispersed species, a certain proportion of In2O3 crystals can be observed by XRD, which is higher for In/ZSM5. This zeolite presents a lower threshold dispersion capacity. Wider and asymmetric XPS In 3d5/2 signals indicate the presence of two surface indium species, one of them with a similar behavior to that of bulk oxide albeit not equal, and the other strongly interacting with the zeolite. The high temperature treatment does not modify the amount of surface indium species but changes their relative proportions. The quantity of highly dispersed species is increased on In/mordenite while the opposite occurs as regards on In/ZSM5. This latter zeolite is constituted by small, packed crystals with lower superficial acidic OH groups, which could originate a higher amount of voluminous polynuclear indium cations remaining on the zeolite crystal surface during impregnation, thus provoking the higher proportion of In2O3 outside channels after OSSIE. Structural modifications are also observed by FTIR being higher for mordenite, such as OH depletion by solid-state exchange, dehydroxilation and creation of extra-framework Al OH species.